Conservation archaeogenomics: ancient DNA and biodiversity in the Anthropocene. (September 2015) - Hofman, Courtney A.; Rick, Torben C.; Fleischer, Robert C.; Maldonado, Jesús E.
Highlights Conservation archaeogenomics integrates archaeological data sets with genomics. We focus on population and distribution changes, translocations, and extinction. We explore archaeogenomics of ancient disease ecology and reconstruction of paleoecosystems. Archaeogenomic data can inform conservation and management in the Anthropocene.